Investigating the feasibility and acceptability of health psychology-informed obesity training for medical students. Issue 3 (2nd April 2016) - Chisholm, Anna; Hart, Jo; Mann, Karen; Perry, Mark; Duthie, Harriet; Rezvani, Leila; Peters, Sarah
Abstract : Health psychologists have succeeded in identifying theory-congruent behaviour change techniques (BCTs) to prevent and reduce lifestyle-related illnesses, such as cardiovascular disease, cancers and diabetes. Obesity management discussions between doctors and patients can be challenging and are often avoided. Despite a clear training need, it is unknown how best to tailor BCT research findings to inform obesity-management training for future healthcare professionals. The primary objective of this descriptive study was to gather information on the feasibility and acceptability of delivering and evaluating health psychology-informed obesity training to UK medical students. Medical students ( n  = 41) attended an obesity management session delivered by GP tutors. Sessions were audio-recorded to enable fidelity checks. Acceptability of training was explored qualitatively. Tutors consistently delivered training according to the intervention protocol; and students and tutors found the training highly acceptable. This psychology-informed training can be delivered successfully by GP tutors and further research is warranted to explore its efficacy.